2020
DOI: 10.1111/nicc.12542
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyethylene cover on the treatment of exposure keratopathy in ICU

Abstract: Background: Exposure keratopathy may lead to serious complications such as microbial keratitis, corneal perforation, and visual impairment if not treated.Aim: To compare the effect of carbomer eye drops when used alone and in combination with polyethylene covers in the healing of exposure keratopathy.Methods: A single blind randomized-controlled trial (RCT) in two intensive care units (ICUs) was carried out in a university hospital in Western Turkey between September 2011 and December 2012. The control group r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…There are many risk factors to weaken the mechanism of eye protection in coma patients in ICU, which are prone to eye diseases [28,29]. The routine eye care plan is to use eye drops in the daytime and eye ointment to close the eyelids at night, but the effect of clinical intervention is not ideal [30,31]. Figure 5: Forest plot: comparison of incidence of corneal injury between polyethylene cover group and eye gel group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many risk factors to weaken the mechanism of eye protection in coma patients in ICU, which are prone to eye diseases [28,29]. The routine eye care plan is to use eye drops in the daytime and eye ointment to close the eyelids at night, but the effect of clinical intervention is not ideal [30,31]. Figure 5: Forest plot: comparison of incidence of corneal injury between polyethylene cover group and eye gel group.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the polyethylene cover group was more effective than the control group in reducing the risk of occurrence of corneal injury [16]. In one randomized controlled trial by Kocaçal et al [30], the control group received only carbomer eye drops while the intervention group received both carbomer eye drops and polyethylene covers; the authors found that carbomer eye drops, when used in combination with polyethylene covers, were effective in managing exposure keratopathy.…”
Section: Computational and Mathematical Methods In Medicinementioning
confidence: 99%
“…Carbomer, an acrylic acid polymers eye drops, when used in combination with polyethylene covers, were effective in managing exposure keratopathy. 3,[19][20][21][22][23][24] Surgical treatment: Surgical options as of punctal plugs, tarsorrhaphy, eyelid reconstruction, Gold or platinum weight implant, orbital decompression, conjunctival flap, amniotic membrane graft, even corneal transplantation may require according to need. If adequate corneal protection cannot be achieved with a combination of taping and lubrication temporary suturing of the lids may be the good option.…”
Section: Drug Treatmentmentioning
confidence: 99%
“…Unfortunately, healthcare professionals in different countries use different criteria when selecting eye care interventions in ICUs [ 3 , 8 ]. Various studies have warned that eye care regimens are not always safe and there is no adequate evidence for the best eye care interventions [ 9 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%